Bright Electrogenerated Chemiluminescence of a Bis‐Donor Quadrupolar Spirofluorene Dye and Its Nanoparticles. Issue 36 (11th July 2016) - Li, Haidong; Daniel, Jonathan; Verlhac, Jean‐Baptiste; Blanchard‐Desce, Mireille; Sojic, Neso
Abstract: A series of symmetric fluorescent dyes built from a spirofluorene core bearing electroactive end groups and having different conjugated linkers were prepared with a view to their use as building blocks for the preparation of electrochemiluminescent (ECL) dyes and nanoparticles. Their electrochemical, spectroelectrochemical, and ECL properties were first investigated in solution, and structure/activity relationships were derived. The electrochemical and ECL properties show drastic variation that could be tuned by means of the nature of the π‐conjugated system, the end groups, and the core. In this series, highly fluorescent dye1 based on a spirofluorene core and triphenylamine end groups connected via thiophene moieties shows the most promising and intriguing properties. Dye1 is reversibly oxidized in three well‐separated steps and generates a very intense and large ECL signal. Its ECL efficiency is 4.5 times higher than that of the reference compound [Ru(bpy)3 ] 2+ (bpy=2, 2′‐bipyridine). This remarkably high efficiency is due to the very good stability of the higher oxidized states and it makes1 a very bright organic ECL luminophore. In addition, thanks to its molecular structure, this dye retains fluorescence after nanoprecipitation in water, which leads to fluorescent organic nanoparticles (FONs). The redox behavior of these FONs shows oxidation waves consistent with the initial molecular species. Finally, ECL from FONs made of1 was recorded in water and strong ECL nanoemitters are thus obtained. Abstract : Stay stable and be excited ! A series of blue‐ to yellow‐emitting symmetrical luminophores built from a spirofluorene core connected to terminal groups via thiophene moieties was synthesized and studied. Only quadrupolar derivatives having donor end groups show stable higher oxidation states, which lead to intense electrogenerated chemiluminescence (ECL) emission (see figure). The molecular confinement of these luminophores in fluorescent nanoparticles gives strong ECL nanoemitters.